The COVID-19 Paradox and Exit Strategy for Nepal - Thakur, Rahul Kumar; Singh, Rajshree; Shrestha, Gambhir; Gautam, Swotantra; Singh, Sunil Kumar (Europasian Journal of Medical Sciences, 2020)
Nepal’s challenges in combating the COVID-19 pandemic include a fragile economy, inadequate preparedness, open borders with India, and China. So far, Nepal has a toll of 22972 cases with 75 deaths as of August 10, 2020. Although, certain postulates like innate factors and the difference in virulence among different strains may have some protective effect as shown by the mild clinical picture in COVID-19 affected Nepalese citizens; the escalation of the daily number of cases is very alarming when the active cases in most of the countries are decreasing. So far, the cases have an increasing trend which shows that the government’s strategies are not working in favor of limiting the disease. This paper reviews how Nepal is tackling pandemic, comparing its strategy with the global scenario and reviewing efficiency of our previously adopted measures with an aim to understand the paradox of unique trend of pandemic in the South Asian region. With unsatisfactory results of current steps and injured economy, Nepal needs revise its strategy especially addressing the areas that need strengthening and incorporate this with the current re-opening plans as we move towards normalcy. Therefore, the government needs to come up with effective strategies including mitigation, preparedness, response, and recovery to manage this global pandemic.